Two new epimers of C15-acetogenin, 4-epi-isolaurallene and 4-epi-itomanallene A as diastereomeric model - Phan, Chin Soon; Takashi Kamada; Charles S. Vairappan (Taylor & Francis, 2020)
Two new C15-acetogenins, 4-epi-isolaurallene (1) and 4-epi-itomanallene A (2) were isolated from a population of marine red alga Laurencia nangii Masuda from Carrington Reef. The structures of these compounds were determined intensively by NMR and HRESIMS data. Their configurations were elucidated by detailed comparison of chemical shifts, germinal protons splitting and NOE correlations with known and synthesized analogues. In addition, antibacterial activities of these compounds were evaluated. These compounds would serve as diastereomeric models for future reference. Since the isolaurallene, neolaurallene, 9-acetoxy-1,10,12-tribromo-4,7:6,13-bisepoxypentadeca-1,2-diene, itomanallene A and laurendecumallene A were isolated, compounds 1 and 2 were the sixth example of C15-acetogenin with dioxabicyclo[7.3.0]dodecene skeleton.